In-between forest expansion and cropland decline: A revised USLE model for soil erosion risk under land-use change in a Mediterranean region. (December 2016) - Mancino, Giuseppe; Nolè, Angelo; Salvati, Luca; Ferrara, Agostino
Abstract: The present study illustrates an original approach for the long-term assessment of soil erosion risk under land-use changes in a Mediterranean region (Matera, southern Italy). The study has been focused on the implementation of a modified Universal Soil Loss Equation (USLE) model at three time points (1960, 1990, 2010) with the objective to evaluate the contribution of each component to model's performance and model outcomes' reliability. A modified USLE model was proposed for the assessment of soil erosion risk, based on the simplification of model's parameters and the use of high spatial resolution datasets. Spatio-temporal variability in the model's outcomes was analyzed for basic land-use classes. Our approach has improved model's flexibility with the use of high spatial resolution layers, producing reliable long-term estimates of soil loss for the study area.